Bodies inhabited by the same flesh: anthropological implications of Michel Henry's theory of corporality - Llorente Cardo, Jaime (Estudios de Filosofía, 2016)
The present study tries to explain the anthropological assumptions implicitly contained in Michel Henry´'s ontology of corporality and specifically in his theory concerning the possibility of a subjectively determined body. In order to achieve this, we examine previously four paradigms regarding the theory of corporality (to be specific, those proposed by Descartes, Sartre, Merleau-Ponty and Heidegger), highlighting their respective tacit implications on the essence of man. From this criticism addressed by Henry to these four models of reflection concerning the corporal, derives a unitary conception of the human phenomenon, as well as a rehabilitation of the ontological status of subjectivity.